Ecoturist Potential and Some Problems in the Development of the Bakhmal State Forestry - Shukurboevna Sanaeva, Lola; Navfal Sodik ugli, Jalilov (American Journal of Biology and Natural Sciences, 2026)
In the Jizzakh region, there are 4 protected natural areas and 5 state forestry enterprises, of which the Bakhmal State Forestry enterprise is of particular importance due to its great ecotourism potential. The organization of ecotourism and other special types of tourism in such natural places plays a key role not only in the economic and social development of the region, but also in the protection of natural resources. The effective organization and sustainable management of ecotourism in such territories play a crucial role not only in stimulating regional economic growth and increasing local employment, but also in ensuring the conservation of natural resources and biodiversity. In particular, ecotourism contributes to reducing anthropogenic pressure on fragile ecosystems through regulated recreational use and environmental awareness among visitors. Furthermore, the development of ecotourism infrastructure in forestry enterprises, especially in the Bakhmal State Forestry area, can enhance the integration of environmental protection with socio-economic benefits. Scientific approaches to planning ecotourism activities, including zoning, carrying capacity assessment, and ecosystem monitoring, are essential for maintaining ecological balance. Thus, the rational use of natural resources through ecotourism represents an effective strategy for achieving sustainable development in the Jizzakh region, combining environmental conservation with economic and social advancement.